2016
DOI: 10.1158/1078-0432.ccr-15-1762
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Preclinical Trials in BRAF Inhibitor–Resistant Patient-Derived Xenograft Models Identify Second-Line Combination Therapies

Abstract: Purpose To test second-line personalized medicine combination therapies, based on genomic and proteomic data, in patient-derived xenograft (PDX) models. Methods We established 12 PDX from BRAF inhibitor progressed melanoma patients. Following expansion, PDX were analyzed using targeted sequencing and reverse phase protein arrays (RPPA). By using multi-arm pre-clinical trial designs, we identified efficacious precision medicine approaches. Results We identified alterations previously described as drivers of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(122 citation statements)
references
References 48 publications
2
120
0
Order By: Relevance
“…Pharmacologic data in colorectal cancer cells indicated that MET inhibition alone was ineffective to overcome resistance and that crizotinib should be combined with BRAF blockade to affect the proliferation of MET-overexpressing cells in both short-term and long-term growth assays. This is consistent with what has been reported very recently in BRAFi-resistant melanoma patient-derived xenograft models, in which only combined vertical blockade of the pathway with MET and BRAFi was shown to induce durable regression in mice ( 23 ).…”
Section: Discussionsupporting
confidence: 92%
“…Pharmacologic data in colorectal cancer cells indicated that MET inhibition alone was ineffective to overcome resistance and that crizotinib should be combined with BRAF blockade to affect the proliferation of MET-overexpressing cells in both short-term and long-term growth assays. This is consistent with what has been reported very recently in BRAFi-resistant melanoma patient-derived xenograft models, in which only combined vertical blockade of the pathway with MET and BRAFi was shown to induce durable regression in mice ( 23 ).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, ERK inhibition may provide the opportunity to avoid or overcome resistance from upstream mechanisms, as it is the most distal master kinase of this signaling pathway. This is supported by preclinical evidence that inhibition of ERK by small-molecule inhibitors acted to both inhibit the emergence of resistance and overcome acquired resistance to BRAF and MEK inhibitors (34)(35)(36)(37)(38)(39).…”
Section: Introductionmentioning
confidence: 83%
“…In addition, Krepler and colleagues reported on 12 patient-derived tumor xenograft (PDX) models established from BRAF-mutated melanomas upon progression on BRAF inhibitor therapy (53). Among other changes detected by next-generation sequencing (Foundation One), MET amplification (copy number ranging from 9-63) was noted in 3 PDX models, and increased phosphorylated MET signal was detected in at least one of the PDX models in which capmatinib MET inhibitor therapy demonstrated success.…”
Section: Braf-mutated Tumorsmentioning
confidence: 99%